Ecological And Economic Productivity Agrosilvopastura In Manimbahoi And Sicini Village Of Parigi And Gowa District - Ramalhino Lelo da Cruz; Syamsuddin Millang; Muhammad Dassir (Jurnal Teknologi Pangan dan Ilmu Pertanian, 2024)
Agrosilvopastura as one of the branches of the agroforestry system is one of the land management systems that may be offered to overcome the problems arising from land conversion and simultaneously to overcome the problem of food availability. Manimbahoi and Sicini villages located in Parigi of Gowa Regency, where both villages have the potential of long standing agrosilvopastura system on brand lands, this research is to know (1) Management of agrosilvopastura (2) Level of diversity and value of agrosilvopastura ecological productivity. (3) Economic productivity resulting from agrosilvopastura management in meeting the daily needs and increasing the income of the local community. Methods of field survey research interviewed 30 respondents with purposive sampling and plot measuring 20X20 m to determine ecological and economical productivity and statistical analysis to determine the diversity ecological and economic income. The results of the research show the diversity in Manimbahoi village of 1.2 and 1.3 and 1.3, respectively, are at a low level of diversity. Sicini village, 1.7 pole 1.5 trees are of medium diversity, while 1, 3 stakes are at a low level of diversity while from the questionnaire found acceptance of Agrosilvopastura management of the economical productivity of Manimbahoi and Sicini Village of Rp. 11,112,000 every month, the total revenue of agriculture sector and Sicini Village farm is Rp. 6,446,000 every month. Forestry sector revenue does not exist, because farmers do not know the market network to sell forest products, farmers only use their own for household needs